Analisis Perbandingan Kesehatan Bank Sebelum dan Selama Masa Pandemi Covid-19 Mengggunakan Metode RGEC Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia - Rika Alfita Sari; Efni Cerya (Universitas Negeri Padang, 2023)
This study aims to compare the health of banks before and during the COVID-19 pandemic using the RGEC method on banks listed on the Indonesia Stock Exchange. This research is included in quantitative research with comparative analysis. By using the SPSS 25 program, I process data from the annual financial statements and notes to financial statements obtained from the website www.idx.com. This research uses Pairet Sample T-test analysis. The results of this study indicate that there is no significant difference between bank health and the NPL and CAR ratios, but significant differences in the LDR, ROA, and NIM ratios before and during the Covid-19 pandemic.